Analisis Tingkat Kriminalitas di Jawa Tengah dengan Pendekatan Distribusi Poisson dan Binomial Negatif - kusuma, Bagus; Tampubolon, Elza Ully Tiara; Alfarisi, Salman (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study analyses the influence of factors causing crime in Central Java Province in 2022, with variables including poverty, population density, education, Gross Regional Domestic Product (GRDP), unemployment rate, and food and non-food consumption. Crime in this region is a social issue that needs attention, given the impact it has on both the economy and social community. Criminality data in the form of count data is analysed using Poisson and Negative Binomial regression to overcome the problem of overdispersion, which allows the model to more accurately estimate the relationship between variables. The results showed that the Negative Binomial regression model was better than Poisson regression, based on the AIC (Akaike Information Criteria) value. The variables of poverty and education were found to have a significant influence on crime rates, indicating the importance of social and educational policies in reducing crime rates. Meanwhile, the variables of population density, GRDP, unemployment rate, and food consumption showed no significant effect. These findings provide important insights for the government in formulating policies aimed at reducing crime rates and improving social stability in Central Java Province. This research is expected to be the basis for the development of data-based policies to improve the welfare of the community.